Counseling intervention for native mothers with autism spectrum disorder (asd) children - Chan Wei Sian; Jamayah Saili (RedWhite Press, 2019)
The purpose of the study was to explore the experiences of native mothers with autistic children in Kuching, Sarawak. The research focused on the challenges faced by native mothers with autistic children, their coping strategies, and participation in counseling intervention. This is a qualitative-based research with three native mothers with autistic children, employing approximately 30 until 45 minutes semi-structured interview sessions. Outcome of the interview sessions were categorized into four major themes and nine sub-themes. Recommendation of counseling intervention include psychoeducational, which aim to provide information to native mothers with regards to autism-related knowledge, skills, and techniques to handling autistic children.